Non-linear fluid flow through rough-walled fractures - Javadi, M.; Sharifzadeh, Mostafa; Shahriar, K.; Mehrjooei, M. (n/a, 2009)
Fractures in rock mass are the main flow paths and introduce as a most important attribute in rock mass hydraulic behavior. Hydraulic properties of rock mass are important in civil, mining, and environmental such as Isolation of hazardous and nuclear waste, petroleum and geothermal energy. In this paper, single-phase fluid flow through a rock fracture was studied. Computational domain for an artificial three-dimensional fracture was generated and used for numerical fluid flow simulations. Both laminar and turbulent flow simulations were performed for a wide range of inlet velocities. The results show that the relation between pressure drop and flow rate has a quadratic polynomial form and Forchheimer law was fitted very well to flow simulation results. Also the predicted static pressure drop for turbulent flow simulation was roughly 3% to 17% more than those predicted with laminar flow simulation at Reynolds number of 4.5 to 89.5, respectively.